2017
DOI: 10.1002/mnfr.201700322
|View full text |Cite
|
Sign up to set email alerts
|

Nutrikinetics of Isoflavone Metabolites After Fermented Soybean Product (Cheonggukjang) Ingestion in Ovariectomized Mice

Abstract: ScopeCheonggukjang (CGJ) is a soybean‐based quick‐fermented food popular in Korea that contains a variety of biologically active compounds including isoflavones and saponins. Isoflavone bioavailability may be important for the bone health of postmenopausal women; therefore, the aim of this study is to evaluate the influence of fermentation on the isoflavone metabolite nutrikinetic profile after single dose CGJ or unfermented soybean administration in ovariectomized (OVX) and sham mice.Methods and resultsWe ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…An imbalance of estrogen may be triggered by the bioavailability of nutrients (Lee et al., ; O'Loughlin, & Morris, ). Our previous study confirmed that the bioavailability of isoflavones differed significantly between sham‐operated and ovariectomized (OVX) rats administered the CGJ, which suggested that OVX affected the bioavailability of isoflavones (Lee et al., ). It is also necessary to compare the bioavailability of isoflavones in long‐term fermented soybean foods such as DJ with the results from short‐term fermented soybean foods (CGJ).…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…An imbalance of estrogen may be triggered by the bioavailability of nutrients (Lee et al., ; O'Loughlin, & Morris, ). Our previous study confirmed that the bioavailability of isoflavones differed significantly between sham‐operated and ovariectomized (OVX) rats administered the CGJ, which suggested that OVX affected the bioavailability of isoflavones (Lee et al., ). It is also necessary to compare the bioavailability of isoflavones in long‐term fermented soybean foods such as DJ with the results from short‐term fermented soybean foods (CGJ).…”
Section: Introductionsupporting
confidence: 77%
“…Previous studies confirmed that isoflavones, which are the functional components of soybeans, are converted to aglycones after fermentation, and that such structural changes improve the bioavailability of isoflavones (Chun et al., ; Lee et al., ). This study investigated the bioavailability of isoflavones upon ingesting it in a representative Korean fermented soybean paste produced by long‐term fermentation in OVX rats.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations